2018
DOI: 10.1186/s12968-018-0484-5
|View full text |Cite
|
Sign up to set email alerts
|

Society for Cardiovascular Magnetic Resonance (SCMR) expert consensus for CMR imaging endpoints in clinical research: part I - analytical validation and clinical qualification

Abstract: Cardiovascular disease remains a leading cause of morbidity and mortality globally. Changing natural history of the disease due to improved care of acute conditions and ageing population necessitates new strategies to tackle conditions which have more chronic and indolent course. These include an increased deployment of safe screening methods, life-long surveillance, and monitoring of both disease activity and tailored-treatment, by way of increasingly personalized medical care. Cardiovascular magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 101 publications
0
99
0
4
Order By: Relevance
“…This current study includes a thorough quantitative analysis of postinfarction scars. The values ​​of absolute and relative mass of scars, gray zones, and segments with transmural fibrosis do not significantly differentiate the patients with and without VT (Table 1) which is comparable to the results obtained by Perez‐David 22 and different from those by Boyé et al, 21 Di Bella et al, 23 and Lønborg et al 24 This is likely due to methodology which was not consistent in all the studies with the recommendations of the Society of Cardiovascular Magnetic Resonance (SCMR) 25,26 . We believe that it is not about the quantity of heterogeneous tissue in general, but only these parts which connect to the healthy myocardium and thus facilitate for a wavefront to enter, propagate at a lower speed than the rest of the myocardium and exit belatedly.…”
Section: Discussionmentioning
confidence: 51%
“…This current study includes a thorough quantitative analysis of postinfarction scars. The values ​​of absolute and relative mass of scars, gray zones, and segments with transmural fibrosis do not significantly differentiate the patients with and without VT (Table 1) which is comparable to the results obtained by Perez‐David 22 and different from those by Boyé et al, 21 Di Bella et al, 23 and Lønborg et al 24 This is likely due to methodology which was not consistent in all the studies with the recommendations of the Society of Cardiovascular Magnetic Resonance (SCMR) 25,26 . We believe that it is not about the quantity of heterogeneous tissue in general, but only these parts which connect to the healthy myocardium and thus facilitate for a wavefront to enter, propagate at a lower speed than the rest of the myocardium and exit belatedly.…”
Section: Discussionmentioning
confidence: 51%
“…Treatment up-titration of immunosuppressive therapy, optimal anti-remodeling therapy 4 , exercise restriction…”
Section: Diagnosis Of Autoimmune Myopericarditismentioning
confidence: 99%
“…Tapering of immunosuppressive therapy, continue optimal anti-remodeling therapy 4 , discontinuation of colchicine. Follow-up CMR in 6 months Fig.…”
Section: No Cmr-evidence Of Autoimmune Myopericarditismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Bai et al recently demonstrated that CNN can provide a performance on par with human experts in analyzing cine cardiovascular magnetic resonance (CMR) data (5). Cine CMR data typically has high spatial temporal resolution, excellent SNR, and consistent bloodmyocardium CNR throughout the cardiac cycle, which is why cine CMR is the gold standard for assessment of ventricular function, volumes, mass, and ejection fraction (7).…”
Section: Introductionmentioning
confidence: 99%